Assessing crop production and input use patterns in Ghana: What can we learn from the Ghana living standards survey - Quiñones, Esteban J.; Diao, Xinshen (International Food Policy Research Institute, 2011)
Agriculture in Ghana accounts for about 40 percent of national economy, three quarters of export earnings, and employs 60 percent of the labor force. Agriculture is the backbone of the economy (McKay and Aryeetey, 2004) and the sector has served as the main driver for the growth over the last two decades (World Bank, 2007). Moreover, agriculture is the most important sector for poverty reduction and has helped the country become the first Sub-Saharan African country to achieve the first objective of Millennium Development Goals (MDG1) by halving the country's 1990 poverty rate before the 2015 target year.